Measurment of earnini Quality in Commercial Banking - عواد سعد سلمان (Journal of Economics and Administrative Sciences, 2011)
The importance of earnings quality begin increase in recent year . Particulary after collapse the big companies in U.S.A When the Stock Prices of this Companies negative impact after reporting of transitory & unrealized earnings in the iterim reports , in the same time took to this earnings as absis of Future Predictions . Many of acadmic researchers discusses empirical measures that used to assessments of earnings quality from the perspective of decision usefulness that represent core of FASB’s conceptual Framework , and to the economic – based definition of earnings , developed by (Hicks) in 1939. Tise research attempt to test som of earnings quality measures in commercial banks of Iraq through three approaches : Financial ratios , Accrual approach , and Statistices approach . The rescarch Find important diversity in the results of three approaches . However the overall results assert to exist an high quality in earning of commercial banks of Iraq .